DETERMINAN KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI TERDAFTAR DI BEI - Yelza Diasca; Yeti Apriliawati (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
This study aims to test empirically and determine the effect of financial distress, firm size, profitability, firm growth, proportion of independent commissioners, and leverage on accounting conservatism partially and simultaneously. The population of this study are manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the 2015-2020 period. The selected research sample is 30 companies with sample selection based on purposive sampling technique according to certain predetermined criteria. This study uses multiple regression analysis to determine the magnitude of the influence of the independent variable on the dependent variable. Statistical analysis tool is software IBM SPSS version 25 for windows. The results showed that financial distress and company growth had a positive and significant effect on accounting conservatism, while firm size, profitability, proportion of Independent Commissioners, and leverage had no positive and significant effect on accounting conservatism.